FasL and TRAIL signaling in the skin during cutaneous leishmaniasis - implications for tissue immunopathology and infectious control - Rethi, Bence; Eidsmo, Liv (Frontiers in Immunology, 2012)
Cutaneous leishmaniasis (CL) is associated with chronic inflammation and ulceration of the skin. Tissue macrophages serve as host cells and immune activation is necessary for parasite clearance. The balance between immune-mediated tissue destruction and successful clearance of infection is delicate. Ulceration has been proposed to be a result of infiltration of activated immune cells into the skin. FasL and TRAIL play a dual role in skin homeostasis through induction of apoptosis as well as pro-inflammatory signalling. During leishmaniasis, dysregulation of both FasL and TRAIL has been described by us and others but the resulting pathogenic effects in the skin during human leishmaniasis are not fully elucidated. Targeting disease specific immune deviations has proven to be a promising new approach for the therapy of autoimmune diseases. Potentially, targeting FasL or TRAIL in combination with microcidals could offer a future treatment strategy to reduce the disfiguring immunopathology associated with cutaneous leishmaniasis. In this minireview we will discuss how FasL and TRAIL induced signalling may influence on the extent of tissue inflammation and the efficacy of parasite clearance in leishmaniasis.